Abortion among women living with or not living with HIV/AIDS users of public health services in São Paulo municipality: prevalence, contexts and reasons - Adriana de Araujo Pinho; Wilza Vieira Villela; Regina Maria Barbosa; Simone Souza Monteiro
Abstract Objectives: we investigated the lifetime prevalence of abortion and life contexts and reasons reported for first abortion among women living (WLHA) and not living with HIV/AIDS(WNLHA). Methods: representative samples of 975 users of public health care reference network for HIV/AIDS and of 1,003 users of the primary care public services in São Paulo municipality were selected by cluster-stratified sampling and answered an electronic socio-behavioral questionnaire. Results: the prevalence of abortion was 11.9% (CI95%9.8-13.9) among WLHA and 3.0% (CI95%2.4-5.7) for WNLHA.Most abortions (128) among WLHA occurred before diagnosis and 28 after diagnosis or during pregnancy when diagnosis was given. The majority of women did not use any contraception at the time of the first abortion. The use of misoprostol was the most reported method. Having HIV was very important in deciding to abort for half of the WLHA. Absence of marital life and the lack of desire to have children were the most reported reasons by both groups. Conclusions: the similarity in contexts and reasons to abort among WLHA and WNLHA suggests that they share experiences molded by gender and social inequalities that affect their ability to access sexual and reproductive health resources and services.